Rowing ergometer training for combat sports - Kendall, K. L.; Fukuda, D. H. (Strength and Conditioning Journal, 2011)
Rowing ergometer training provides a basis for combat athletes to improve aerobic and anaerobic fitness while maintaining lean body mass and decreasing fat mass. The specific needs of combat athletes may be met by training on the ergometer because it involves the coordination of both the upper and the lower body to develop maximal strength, speed, and power.